Relationship Between the 2019 Ridgecrest, California, MW7.1 Earthquake and Its MW6.4 Foreshock Sequence - Jianchang Zheng; Zhengshuai Zhang; Xiaohan Li (Entropy)
The 2019 Ridgecrest MW7.1 earthquake has received significant attention due to its complex fault activity. It is also noticeable for its MW6.4 foreshock sequence. There are intricate dynamic relationships between earthquakes in such vigorous sequences. Based on the relocated catalogue, we adopt the nearest neighbour algorithm to analyze its foreshock and aftershock sequences. Detailed links and family structures of the sequence are obtained. The results show that a MW5.0 event at 03:16 (UTC) on 6 July is a direct foreshock of the MW7.1 mainshock. It is likely related to barriers on the northwest-striking fault. The MW6.4 event on 4 July is characterized as a complex conjugate rupture. Notably, a magnitude 4.0 event occurred on the northwest-striking fault before the MW6.4 event, establishing it as a direct foreshock. The Ridgecrest sequence is predominantly influenced by northwest fault activity. It first caused small fractures on the northwest-striking fault. Then, it triggered conjugate slips on the southwest-striking fault. Lastly, it led to larger ruptures on the northwest-striking fault.